2010
DOI: 10.1016/j.ejphar.2010.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of bradykinin receptors in rat bronchia via IκB kinase-mediated inflammatory signaling pathway

Abstract: Thus, IKK inhibition might be a promising approach for treatment of airway inflammation and airway hyperresponsiveness that are often seen in asthmatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Theoretically, inhibition of the MAPK/NF-B signal mechanisms that mediate upregulation of kinin receptors and subsequent AHR will exert similar therapeutic effects as kinin receptor antagonists. In addition to this, MAPK/NF-B inhibition suppresses not only kinin receptor upregulation and AHR to kinins [8,116,118], but also inhibits inflammatory mediator expression [50,118,120], airway fibroblast [145] and smooth muscle cell proliferation [146][147][148] as well as airway remodeling [149][150][151]. Taken all together, this suggests that inhibition of MAPK/NF-B-dependent kinin receptor upregulation is a better therapeutic strategy than blocking kinin receptors using their antagonists for the treatment of asthmatic and inflammatory airways.…”
Section: New Therapeutic Targets For Treatment Of Ahrmentioning
confidence: 82%
See 3 more Smart Citations
“…Theoretically, inhibition of the MAPK/NF-B signal mechanisms that mediate upregulation of kinin receptors and subsequent AHR will exert similar therapeutic effects as kinin receptor antagonists. In addition to this, MAPK/NF-B inhibition suppresses not only kinin receptor upregulation and AHR to kinins [8,116,118], but also inhibits inflammatory mediator expression [50,118,120], airway fibroblast [145] and smooth muscle cell proliferation [146][147][148] as well as airway remodeling [149][150][151]. Taken all together, this suggests that inhibition of MAPK/NF-B-dependent kinin receptor upregulation is a better therapeutic strategy than blocking kinin receptors using their antagonists for the treatment of asthmatic and inflammatory airways.…”
Section: New Therapeutic Targets For Treatment Of Ahrmentioning
confidence: 82%
“…It is well-known that activation of MAPK subsequently results in phosphorylation (activation) of down-stream transcriptional factor NF-B, which mediates transcription and translation of proinflammatory mediators [117] and de novo synthesis of kinin receptors in airway [8,116,118]. Clinical studies demonstrate that phosphorylated ERK1/2 and p38 MAPK correlate to the airway disease severity in asthma [48,119], suggesting activation of MAPK signaling pathways strongly associates with AHR and asthma exacerbation.…”
Section: Mapk/nf-b Signaling In Ahr Developmentmentioning
confidence: 95%
See 2 more Smart Citations
“…Among them, the JNK signaling is demonstrated to tightly regulate the TP receptor related inflammation (Bayat et al, 2008;Kumar et al, 2005) in vasculature and the JNK inhibitor SP600125 exerts effects on allergen-induced airway inflammation and remodeling (Eynott et al, 2004;Nath et al, 2005). A common feature associated with the regulation of airway smooth muscle contraction is a change in intracellular Ca Previously, we have demonstrated that organ culture induced airway hyperresponsiveness to bradykinin occurs via the up-regulated bradykinin receptors (Lei et al, 2010). The present study was designed to investigate if organ culture affects TP receptor mediated airway contractile responses focusing on the roles of transcription and MAPK activity and calcium channel activities.…”
Section: Introductionmentioning
confidence: 99%